The reception of indigenous literature developed with the Receptive Reading Method (Research, Society and Development, 2020)
The teaching of Portuguese language should include the study of indigenous culture, from public and private schools, enabling cultural inclusion and overcoming the silencing and invisibility of indigenous culture in the educational system, through the reading of literary texts of indigenous authorship and not indigenous. In this study, a didactic sequence is developed, with a pragmatic purpose, to promote activities related to the reading of indigenous literature, in order to answer: how does the reception of indigenous literature occur through the Receptive Reading Method (MRL)? Thus, the objective was to present and validate a proposal for an organization to teach reading of indigenous literature. Thus, it starts from the contextualization of the object of study, problematization and relevance. The theoretical and methodological basis that guided the research is linked to the assumptions of reading indigenous literature by Thiél (2012) and Graúna (2013), to the MRL, by Bordini & Aguiar (1993) anchored in the Aesthetics of the Jauss Reception (1994, 2002). It was possible to observe that the literary modalities used in this study, gave voice to the indigenous author telling his own story, enabling the overcoming of some untruths, a legacy of the common sense of the last 500 years about indigenous peoples. The crossing through the workshops, through the MRL, of the aesthetic experience and of the content, with emphasis on the reflections of indigenous textualities, multimodality and plurality, promoted the expansion of the horizons of students' expectations, bringing them closer to the horizons of non-indigenous and indigenous authors, showing empathy through artistic-literary productions.